Availability and Pride of Mentawai Ethnic Communities for Local Food on Sipora Island - Erwin Erwin; Robi Mitra; Ade Irwandi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The Mentawai ethnic community on Sipora Island is one of the ethnic groups that consume local food passed down from generation to generation by their ancestors. Even though rice and other foods are easy to find, they still make bananas, taro, and toek as their daily staple food. This study aims to determine the availability and pride of the Mentawai ethnic community for local food in the village of Goiso Oinan, Sipora Island, Mentawai Islands Regency, West Sumatra Province for local food. This research was conducted in the Goiso Oinan village community on Sipora Island for 50 days, starting on August 10 - September 29, 2022, with a total of 20 informants divided into eight key informants and 12 ordinary informants. This study used a qualitative method with purposive sampling and descriptive analysis by explaining the results of ethical research and emic analysis related to the availability and pride of the Mentawai ethnic community for local Food on Sipora Island. Data was collected using observation, in-depth interviews, literature studies, and documentation. Data analysis was carried out in parallel, namely grouping data, reading data carefully, and explaining it in detail. As for the findings of the research results, the availability of local food for the Mentawai ethnic community in the village of Goiso Oinan greatly exceeds that of the people who consume it. The Mentawai ethnic community in the village always maintains this local food for their family's survival. They feel proud of local food as an inheritance from their ancestors, so it is also a must-have food when holding wedding ceremonies, death ceremonies, and other events. Other events.